Taking a peek matters: Surveying the role of information scanning on COVID-19 vaccination intentions - Yafei Zhang; Li Chen; Ge Zhu (Taylor & Francis Group, 2024)
Background The COVID-19 pandemic has been accompanied by an overabundance of information on social media. Information scanning, a less purposive form of information acquisition has not received adequate scholarly attention. It is worthwhile to investigate the role of information scanning in shaping health attitudes and outcomes during the later stages of a public health crisis.Aims This study aimed to examine the critical role of information scanning in affecting individuals' COVID-19 vaccination intentions. We extended the Integrative Model of Behavioral Prediction (IMBP) delineating how information scanning, attitudes, subjective norms, and perceived behavioral control can indirectly influence individuals' vaccination intentions. We also introduced eHealth literacy to our proposed model. Regarding research context, this study contextualized information scanning to COVID-19 vaccine-related information on a popular social media application, WeChat.Methods We conducted a survey in China to answer our research questions. Data were collected via an online survey using the Qualtrics panel between July 2 and July 29, 2021. Self-identified WeChat users above the age of 18 who had not received any COVID-19 vaccines were qualified to participate in this study. Data from 405 participants were used for modeling and analysis.Results EHealth literacy was not directly associated with COVID-19 vaccination intentions. However, an indirect relationship was observed through 1) a single mediation of information scanning, 2) a serial mediation of information scanning and attitudes, and 3) a serial mediation of information scanning and subjective norms.Discussion Our study suggests that information scanning on COVID-19 vaccines is positively associated with individuals' attitudes, subjective norms, perceived behavioral control, and intentions to get the COVID-19 vaccines. Our findings resonate with previous research on the associations between information scanning and IMBP. We also found that individuals' eHealth literacy does not directly predict their COVID-19 vaccination intentions, but the relationship between eHealth literacy and vaccination intentions has to be mediated via information scanning, attitudes, and subjective norms. This finding has challenged some existing research. We argue that the interplay among eHealth literacy, information scanning, and IMBP components varies across different stages of an emerging infectious disease outbreak.